Aplikasi Minyak Sawit Merah sebagai Medium untuk Penumisan Sayur - Putri, Permata Adinda; Rahayu, Winiati Pudji; Adawiyah, Dede Robiatul; Andarwulan, Nuri (Jurnal Teknologi dan Industri Pangan, 2024)
Red palm oil (RPO), processed without bleaching, has a higher total carotenoid content compared to commercial frying oil (CFO), at 500-700 ppm. The use of RPO in household cooking is not widespread due to its different characteristics compared to the commonly used cooking oil. This research aimed to determine the physicochemical characteristics (color, total carotenoid, iodine value, peroxide value, and acid value) and sensory attributes of RPO and CFO, followed by a comparison. Both oils were used in the preparation of pan-fried dishes, specifically pan-fried bean sprouts and pan-fried water spinach. Parameters observed in the pan-fried products included color, total carotenoid, sensory profile, and consumer’s acceptance. The results showed that the total carotenoid content in RPO (520.24±0.52 μg/g for pan-fried water spinach) was higher than in CFO (2.20±0.54 μg/g). However, CFO excelled in other chemical parameters, with a higher iodine value and lower acid and peroxide value. The total carotenoid in pan-fried products processed with RPO (34.52±0.25 μg/g for pan-fried bean sprouts and 37.83±0.05 μg/g for pan-fried water spinach) provided more than 15% of the daily vitamin A requirement per person. Pan-fried products made with RPO showed a sensory profile identical to the oil, and based on the obtained hedonic scores (neutral–slightly liked), products with RPO were not well-accepted by consumers. These results indicate that the application of RPO as a pan-frying medium can enhance its nutritional value due to its high carotenoid content, but it is not well-received sensorially.